Web 2.0 : challenges and opportunities for assessing learning in teacher education programs - Coutinho, Clara Pereira (2012)
In this article, the author presents the results of a project where different Web 2.0 technologies were used as tools for assessing learning in education programs at the University of Minho, Braga, Portugal. The emergence of new skills to better fit the networked information economy presses higher education institutions to invest in digitally rich environments that allow learning to be personalized, taking place in multiple locations and at time that suits the learner. Social web tools prioritize collaboration, participation, and reflection, as well as offer new opportunities for knowledge construction and sharing. But they also demand new pedagogical strategies and forms of assessment that are not consistent with standards that value what is taught instead of what is constructed, what is pre-established instead of was is agreed. To provide rationale for embracing Web 2.0 tools as well as point out forms to create, capture, and assess evidence that results from the integration of such tools in learning and teaching, the author describes sixteen pedagogical experiences and reflects on the affordances and challenges of setting up authentic tasks that engage students in the learning process and embracing digital evidence in different formats for assessing learning outcomes.